CONSTITUTIVE MODEL AND FAILURE PARAMETERS OF TC4 TITANIUM ALLOY UNDER QUASI-STATIC TENSILE - FANG XinWen; GUAN JiaJia (Jixie qiangdu)
Large deformation and fracture processes of materials are often involved in the finite element simulation of high-speed collision. Based on the Johnson-Cook fracture failure model, TC4 titanium alloy samples with different notch sizes were designed, and the fracture strain and stress triaxiality of the samples were studied by combining test and finite element simulation. Speckle was produced during the experiment. The fracture strain of the sample under quasi-static tensile condition was obtained by using two-dimensional digital image correlation（DIC） technique at room temperature. The software Abaqus was used to simulate the quasi-static tensile process and obtain the average stress triaxiality of each sample. The parameters of Johnson-Cook fracture failure model were obtained by fitting the fracture strain with average stress triaxiality. The parameters of the fracture failure model were brought into the Pamcrash software for simulation, the fracture morphology and load-displacement curves of the test and Pamcrash simulation showed good consistency, which verified the correctness of the parameters of the failure model.